The Impact of Sedimentation on the Perak River Shipping Channel on Shipyard Operations - Nafhan Iqbal; Sianturi, Intan; Ratnaningsih, Dyah; Rahayu, Trisnowati (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
Siltation of shipping channels is a problem that can increase shipping safety and security risks and hinder economic activities. One of the causes of siltation is sedimentation, which is the process of deposition solid particles in the form of sand and rocks so that it requires regular maintenance. Especially in the Perak River shipping channel that has occurred quite significantly over the past few years and there has been no dredging until now. The occurrence of sedimentation has a great impact on the operational activities of shipyard companies located along the Perak River shipping channel. The purpose of this study is to find out what are the impacts caused by the sedimentation of the Perak River on shipyard operations. This type of research is a Quantitative research using the SPSS application. The sample of this research is an employee at the shipyard company PT. Dumas Tanjung Perak Shipyard and Pelni Surya Shipyard. In this study, a simple linear regression data analysis technique was used, then the result of the equation Y = 5.943 + 1.112X was obtained. The results of this study show that the impact of sedimentation of shipping channels has a positive and significant effect on shipyard operations. The impact of siltation such as a reduction in the number and size of vessels that can pass through the channel and also increased operational costs for shipyard companies and ship owners due to process delays when waiting for the waters to be independent in the highest tide conditions.